Pembuatan Direktori Kepegawaian Pengadilan Negeri Tindak Pindana Korupsi Padang Kelas 1a - fatahillah, Agung; Desriyeni, Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
This paper discussed about the Making of Directory of Officer of Corruption in Correctional Court of Class 1A Padang. The purpose of writing this paper is to design and produce a printed or book-shaped directory to find information about employee data. The research method used is descriptive method with data collection technique of observation of spaciousness and do not do interview.Based on the analysis of data can be concluded the steps of directory creation as follows: 1) to collect employment data; 2) record data and data input into Microsoft Word; 3) focus on ideas when creating directory books that have been created; 4) create a book framework for directed writing; 5) write the concept of directory creation that is arranged according to the highest to lowest position; 6) determine the subject in the manufacture of directories that is the name of the position; 7) grouping the data that has been collected according to the subject; 8) determine what elements will be included in making directory creation in accordance with the data already obtained; 9) design a directory model; 10) compile and create directory of employees and create cover.Keywords: personnel, directory